2020
DOI: 10.1155/2020/2750258
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Pregnancy in Endemic Regions of Colombia: High Frequency of Asymptomatic and Peri-Urban Infections in Pregnant Women with Malaria

Abstract: Background. Malaria in pregnancy (MiP) has been associated with adverse pregnancy outcomes. There is limited information on MiP in low transmission regions as Colombia. This study aimed to describe the epidemiology of MiP through active surveillance of infections by microscopy and polymerase chain reaction (PCR). Methods. A cross-sectional study was conducted between May 2016 and January 2017 in five municipalities (Apartadó, Turbo, El Bagre, Quibdó, and Tumaco) in Colombia. Pregnant women self-presenting at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
(62 reference statements)
5
18
2
4
Order By: Relevance
“…Forty-nine studies (43.36%) comprised both symptomatic and asymptomatic participants, whereas 26.55% and 30.09% included respectively asymptomatic and symptomatic participants only. Children under 15 years old were targeted in 10.62% of studies, mostly in AFR ( n = 11); pregnant women were investigated in 7.08% in the African Region ( n = 7) [ 18 24 ] and Region of the Americas (AMR) ( n = 1) [ 25 ], and one study (0.88%) was conducted among 4570 women of childbearing age in the Democratic Republic of the Congo (DRC) [ 26 ] (Additional file 3 : Table S3).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies (43.36%) comprised both symptomatic and asymptomatic participants, whereas 26.55% and 30.09% included respectively asymptomatic and symptomatic participants only. Children under 15 years old were targeted in 10.62% of studies, mostly in AFR ( n = 11); pregnant women were investigated in 7.08% in the African Region ( n = 7) [ 18 24 ] and Region of the Americas (AMR) ( n = 1) [ 25 ], and one study (0.88%) was conducted among 4570 women of childbearing age in the Democratic Republic of the Congo (DRC) [ 26 ] (Additional file 3 : Table S3).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…With PCR, the comparison of both species presented the following results: MAP registered an OR of 1.0 (95%CI = 0.7-1.5) and CM 0.7 (95%CI = 0.5-1.1) that indicated a similar prevalence of both species. Finally, among the factors associated with MAP, the area of residence (higher GM in rural areas) [10]; the number of previous pregnancies (more GM in women with a higher number of pregnancies) [12]; the weeks of gestation (lower gestational age in infected women) [10,12]; the number of malaria episodes in the current pregnancy [10,23], in the last year and among partners (higher among infected pregnant women) [10]; and lower birth weight were reported [12]. However, this evidence was not consistent among the studies (even between those carried out in the same endemic area), since other authors did not report statistical differences in MAP according to maternal age [10,15,16,22,24], gestational age [15,16,24], number of pregnancies [15,22], previous episodes of malaria [16,22], parity [16,23,24], weight and height of the newborn [15,16,22,24], neonatal anemia, or preterm delivery [15].…”
Section: Plos Onementioning
confidence: 99%
“…Finally, it is essential to note that the report of the factors associated with MAP was deficient. Some studies reported the association of MAP with the number of pregnancies [14], gestational age [10,12], previous malaria episodes [10,23], and birth weight [12]. However, these findings were not consistent between the studies, so their research should be circumscribed to more local spaces, which allow the identification of possible risk factors specific to each group.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Besidesa, in Colombia, there are few publications on PM, and they concentrate on histopathological and immunological issues [ 8 10 , 22 ]. Epidemiological studies on PM have reported frequencies between 0.3% and 12.8% with TBS (thick blood smear), and 2.7% to 57.3% with PCR (polymerase chain reaction); These studies have focused on the comparison of diagnostic tests, the detection of asymptomatic and submicroscopic infections (positive with PCR and negative with TBS) [ 8 , 16 , 23 25 ]. Knowledge about maternal and neonatal factors and the history of malaria potentially associated with PM has been less explored.…”
Section: Introductionmentioning
confidence: 99%